Succession in the Family Business: The Great Challenge for the Family - Corona, Juan (European Journal of Family Business, 2021)
One of the most significant challenges facing family businesses, and therefore the most studied, is how to successfully manage succession from one generation to the next. The purpose of this article is to allow the vast quantity of evidence and experience to be contextualised, and enable a better understanding of the challenges, the role the new generation plays, the probate process, the preparation of the successor and the importance of family harmony in family business successions. The paper points to the importance to develop new generation leaders as well as the need to carefully consider when to begin with the succession process. It also highlights that preparing the successor is an evolutionary process and that family harmony is critical to succeed in the process.